2021
DOI: 10.1186/s41687-021-00385-z
|View full text |Cite
|
Sign up to set email alerts
|

Burden of mental health symptoms and perceptions of their management in in-centre hemodialysis care: a mixed methods study

Abstract: Background We aimed to describe (1) depressive and anxiety symptom burdens reported by adults on in-centre hemodialysis in Northern Alberta, Canada and (2) patients’ and nurses’ perceptions of managing such symptoms using routine patient-reported outcome measures (PROMs). Methods A longitudinal mixed methods approach was employed. Cluster randomized controlled trial data exposed the prevalence of positive screens (scores ≥ 3) for depressive (PHQ-2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…But Albertans in a different study investigating use of patient-reported outcomes in in-center dialysis also voiced their concerns about privacy for chairside mental health support. 20 Patients’ perspectives spanned the spectrum from feeling like they needed a private environment to feeling like all manner of their health was already discussed in a non-private environment, so why should mental health be any different? Nurse participants in this study held similar views spanning this continuum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But Albertans in a different study investigating use of patient-reported outcomes in in-center dialysis also voiced their concerns about privacy for chairside mental health support. 20 Patients’ perspectives spanned the spectrum from feeling like they needed a private environment to feeling like all manner of their health was already discussed in a non-private environment, so why should mental health be any different? Nurse participants in this study held similar views spanning this continuum.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The most common mental health symptoms reported by people receiving dialysis are depression and anxiety (40% 2 and 11%-52% 1 ), significantly higher than 5% and 3%, respectively, reported by all Canadians. 3 Mental health symptoms are underdiagnosed and undertreated among Canadians on dialysis and deserve attention; 4 - 7 the need for support is now greater.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that PROMs (ESAS-r: Renal/EQ-5D-5L) had the potential to rapidly identify mental health problems. However, there were differing opinions on whether mental health fell within the scope of care of nephrologists and nurses, and there was consensus that more mental health resources were needed [31].…”
Section: Epros In Hemodialysis An Unfinished Businessmentioning
confidence: 99%
“… 24 Furthermore, when the Can-SOLVE CKD Triple I Project identified the top 10 challenges to in-center hemodialysis care, people treated with hemodialysis believed that access to mental health care was a priority challenge to address. 25 However, stigma, siloed care designated by body parts (eg, kidney), dialysis culture, and concerns by providers about scope of practice 24 , 26 have all contributed to this pervasive, multifaceted health service gap. In turn, mental health care of adults treated with dialysis in Canada has been largely unexplored and unaddressed.…”
Section: Introductionmentioning
confidence: 99%